Capturing Ephemeral Assessment Opportunities: An Inquiry into Secondary Mathematics Teachers’ Lived Experiences with Observation of, and Conversations with, Students - Pai, Jimmy (Université d'Ottawa / University of Ottawa, 2017)
This study is influenced by phenomenological approaches, and is an inquiry into secondary mathematics teachers’ lived experiences with ephemeral assessment opportunities such as observations of, and conversations with, students. This phenomenon is explored through the use of reflective journals, semi-structured interviews, and focus group interviews. Two layers of analysis were used to better understand the phenomenon. The first layer focuses on emergent themes of what and how teachers think and do in the moment. The emergent themes were interrelated and categorized into eliciting, interpreting, and acting. The second layer focuses on the emergent factors that contribute to what and how teachers think and do during the ephemeral assessment process. The emergent factors were interrelated and categorized into teacher, student, relationships, and contexts. Through the two layers, the complexity of the ephemeral assessment process has been developed.
Keywords: Assessment; Formative Assessment; Summative Assessment; In-the-moment assessment; Noticing; Classroom Assessment